Promoter of the Lithuanian Music Research - Ramoškaitė, Živilė (Tautosakos darbai, 2020)
Teodoras Brazys (1870–1930) was a priest, organist, choir director, pedagogue, composer, journalist, musicologist researching Lithuanian folklore, publicizing on the church and secular music, and an active social worker. Brazys was the author of the first Lithuanian musical textbooks: the one on musical theory, which had three print runs (in 1920, 1922, and 1925), on harmony (1926), “The Singing School” (1920), and “The Choral School” (1926). He was the first in Lithuania to launch scientific research of folk melodies: his relevant study in German was published in 1918 and in Lithuanian in 1920.Along with his original church music pieces and folksongs harmonized for choirs, Brazys has left a considerable number of folksongs that he recorded. Two bulky collections (LTR 205 and LTR 443) are stored at the Lithuanian Folklore Archives of the Institute of Lithuanian Literature and Folklore, dated approximately by 1918–1919, and comprising about 1350 songs.These collections deserve an exceptional place in the history of folksong recording and publication. Before Brazys, only the priest Antanas Juška (1809–1880) had recorded a number of folksongs along with their melodies. Unfortunately, manuscript recordings of melodies by Juška did not survive; only their copies by other persons that were edited and published in 1900 in Cracow as a collection comprising 1875 melodies have reached us.Recordings of folk melodies by Brazys stand out among the meager folksong melodies’ collections of the time because of their exceptional professionalism. In 2014, the Institute of Lithuanian Literature and Folklore published the first volume of folksongs (entitled “National Songs”), recorded by Brazys, edited by Kostas Aleksynas and Živilė Ramoškaitė. This volume comprised songs from the collection LTR 443, recorded in Kietaviškės parish. Currently, on the 150th anniversary of Brazys, the same editors are about to complete two more volumes. The second volume includes 410 songs performed by a famous folk singer from Dzūkija region Ieva Krukoniūtė, and the third one – over 500 songs recorded in Varėna and Alytus districts. Both volumes are going to be published in 2021.
Keywords: -